Unveiling Luminescent IrI and RhI N‐Heterocyclic Carbene Complexes: Structure, Photophysical Specifics, and Cellular Localization in the Endoplasmic Reticulum. Issue 22 (23rd March 2021) - Daubit, Isabelle Marie; Wortmann, Svenja; Siegmund, Daniel; Hahn, Stephan; Nuernberger, Patrick; Metzler‐Nolte, Nils
Abstract: Complexes of Rh I and Ir I of the [M(COD)(NHC)X] type (where M=Rh or Ir, COD=1, 5‐cyclooctadiene, NHC=N‐heterocyclic carbene, and X=halide) have recently shown promising cytotoxic activities against several cancer cell lines. Initial mechanism of action studies provided some knowledge about their interaction with DNA and proteins. However, information about their cellular localization remains scarce owing to luminescence quenching within this complex type. Herein, the synthesis of two rare examples of luminescent Rh I and Ir I [M(COD)(NHC)I] complexes with 1, 8‐naphthalimide‐based emitting ligands is reported. All new complexes are comprehensively characterized, including with single‐crystal X‐ray structures. Steric crowding in one derivative leads to two distinct rotamers in solution, which apparently can be distinguished both by pronounced NMR shifts and by their respective spectral and temporal emission signatures. When the photophysical properties of these new complexes are exploited for cellular imaging in HT‐29 and PT‐45 cancer cell lines, it is demonstrated that the complexes accumulate predominantly in the endoplasmic reticulum, which is an entirely new finding and provides the first insight into the cellular localization of such Ir I (NHC) complexes. Abstract : Anticancer NHC complexes : Rh I and Ir I N‐heterocyclic carbene (NHC) complexes provide an auspicious class of potential new anticancer agents; however, cellular imaging with luminescent derivatives of these complex types is often hampered by luminescence quenching. Building on an analysis of the parameters for metal‐induced quenching processes, new examples of this complex class are designed with properties suitable for cellular imaging. Their main localization in the endoplasmic reticulum is not only an unprecedented finding but also represents the first ever insight into the cellular localization of Ir(NHC) complexes in the oxidation state +I.